PENGARUH CSR, LIKUIDITAS, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP PENGHINDARAN PAJAK - Rika Juli Arta; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2023)
This research analyzed whether corporate social responsibility, liquidity, profitability, firm size, and leverage affect tax avoidance. The dependent variable in this research is tax avoidance proxied by the cash-effective tax rate. In contrast, the independent variables in this research are corporate social responsibility, liquidity, profitability, and company size. This research used quantitative methods. The population in this research are manufacturing companies on the Indonesia Stock Exchange. The sample selection technique uses purposive sampling. Multiple linear regression analysis is a statistical method used to test the hypothesis in this research. The findings of this research are that corporate social responsibility has a significant positive effect on tax avoidance. Liquidity has a significant negative effect on tax avoidance. Profitability has a significant negative effect on tax avoidance. Company size has a significant positive effect on tax avoidance. Leverage has a significant negative effect on tax avoidance.